Encyclopaedia of the Qurʾān (Qurʾānic studies online, 2007)
Brill's Encyclopaedia of the Qur'an (EQ) combines alphabetically-arranged articles about the contents of the Qur'an. It is an encyclopaedic dictionary of qur'anic terms, concepts, personalities, place names, cultural history and exegesis extended with essays on the most important themes and subjects within qur'anic studies. The Encyclopaedia of the Qur’ān Online is the first comprehensive, multivolume reference work on the Qur’ān to appear in a Western language.